Quake proof building the perfect bridge - Copeland, Gary; Weiss, Dylan; Discovery Channel (Firm); Discovery Channel University; Science Channel (Television network); Cry Havoc Productions ([United States] : Discovery Communications, 2006)
A behind-the-scenes look at modern anti-earthquake preparation, this program documents the replacement of a major section of the San Francisco-Oakland Bay Bridge. Anticipating the 2007 demolition of the bridge's eastern cantilever span, the video shows viewers how the new design and construction will presumably withstand a high-magnitude earthquake. Footage of the construction process accompanies detailed scenes of seismologists and engineers at work--testing bridge columns with a giant'shake table,' predicting the area's next quake, and demonstrating the phenomenon known as liquefaction
Title from title screen
Executive producer, Milt Weiss ; camera and editing, Dylan Weiss
Narrator: Rick Wasserman
Keywords: Bridges -- Design and construction; Earthquake resistant design; Bridge failures -- California -- San Francisco Bay Area